The importance of examining diversity in reflective supervision when working with young children and their families. Issue 5 (3rd September 2018) - Wilson, Karol; Barron, Carla; Wheeler, Rebecca; Jedrzejek, Patricia Estele-Avelini
ABSTRACT: Cultural sensitivity is fundamental to relationship-based interventions where professionals meet with children and families in their homes, neighborhoods, and communities. Understanding how we are different from others and how to engage in meaningful relationships despite those differences is important at all levels of human interaction. Professionals who provide relationship-based intervention benefit from supervision aimed at enhancing their capacity for reflection. Reflective supervision has become a powerful training technique to support the professional's capacity to think deeply about their work with vulnerable infants and families. This article will consider the impact of diversity upon the developing relationship between the reflective supervisor and supervisee. Through use of a supervisory vignette, this article will consider how cultural differences can pose a barrier to the full incorporation of the reflective experience within infant mental health work and professional growth. The authors posit that reflective supervision can support cultural sensitivity, relationship building, professional growth, and positive infant and family outcomes.